An overview: NIR imaging system for medical photogrammetry applications - M. Arif, M. Farid; Setan, Halim; Chong, Albert K. (2006)
To this day, the NIR (Near-Infrared) remains one of the most useful extra-visible bands in the EM (electromagnetic) spectrum. Aerial photogrammetry have long relied on NIR imagery to capture the landscape with the greatest possible clarity over a wide range of atmospheric conditions including some quite unsuitable for visible light photography. But today, with features like low-cost, higher-resolution and hand-held digital cameras with near-infrared (NIR) capability are now readily available for close-range photogframmetry applications. The NIR spectrum (700 to 1000 nanometers) is a tiny part of the overall electro-magnetic spectrum. It is just outside the spectrum seen by the human eye. While it is not possible to see NIR radiation it can be recorded on NIR films or CCDs with special filters. Digital NIR image of vegetations, living things, rocks and man-made objects have a number of positive features over the traditional color or black and white photography. In the past, NIR images were strategically used only because of the expensive and hard-to-find NIR films and high-cost CCDs. However, present CCD cameras require only inexpensive NIR filters to take good NIR images. The paper highlights the current applications and potential of NIR images in photogrammetry for the purpose of medical applications.